Human Papillomavirus E6 and E7: The Cervical Cancer Hallmarks and Targets for Therapy - Pal, Asmita; Kundu, Rita (Frontiers in Microbiology, 2020)
Human papillomavirus (HPV)-induced cervical cancer is a major health issue among women from the poorly/under-developed sectors of the world. It accounts for a high mortality rate, because of its late diagnosis and poor prognosis. Initial establishment and subsequent progression of this form of cancer is completely dependent on two major oncogenes E6 and E7, which is expressed constitutively leading to tumorigenesis. Thus, manipulation of these genes represent the most successful form of cervical cancer therapy. In the present article information on structural, functional and clinical dimensions of E6 and E7 activity have been reviewed. The genome organisation and protein structure of E6 and E7 have been discussed followed by their mechanism to establish the six major cancer hallmarks in cervical tissues for tumour propagation. The later section of this review article deals with the different modes of therapeutics which function by deregulating E6 and E7 activity. Since E6 and E7 are the biomarkers of a cervical cancer cell and are the ones driving the cancer progression, therapeutic approaches targeting E6 and E7 have been proved to be highly efficient in terms of focused removal of abnormally propagating malignant cells. Therapeutics including different forms of vaccines to advanced genome editing techniques which suppress E6 and E7 activity have been found to successfully bring down the population of cervical cancer cells infected with HPV. T-cell mediated immunotherapy is another upcoming successful form of treatment to eradicate HPV infected tumorigenic cells. Additionally, therapeutics using natural compounds from plants or other natural repositories, i.e. phytotherapeutic approaches have also been reviewed here, which prove their anticancer potential through E6 and E7 inhibitory effects. Thus, E6 and E7 repression through any of these methods is a significant approach towards cervical cancer therapy, described in details in this review along with an insight into the signalling pathways and molecular mechanistic of E6 and E7 action.